Odugen: location, etymology and linkage with the Hangai analogue - Mongush, Andrey A. (The New Research of Tuva, 2018)
Odugen or Odugen-Taiga is a well-known territorial name among Tuvans. For the Todzhu reindeer herders of Tuva, Odugen-Taiga is an integral part of their culture and way of life. However, this toponym is absent on topographic or any other maps of the area, the whole of Tuva and adjacent territories. The article deals with the four-fold question of why the toponym does not appear on maps, where exactly it is actually located, what its etymology is and how it is relate to the ancient Turkic Otuken. We present a brief analysis of the published toponymical, etymological and cultural sources about the area called ‘Өдүген’ (Odugen), adding to it the information provided by the locals of the Todzhu district, who were interviewed in 2017. The obtained information is then tested against the hard geological data. It is proved that historically the area named Odugen covered the mountain regions of Central Asia, which showed manifestations of late Cenozoic volcanism. These areas include most part of the mountain systems of Eastern Sayan and Khangai. Historical and folk information about the location of this toponym and geological data on the youngest volcanism both point to the same areas in the Eastern Sayan and Khangai. Linguists have discovered three elements in the etymology of the word, which was formed by joining the Turkic verbal stem ‘өt’ (meaning ‘to defecate’), noun affix ‘(a)k’ (өt+(a)k > өdek: manure; slag, lava [volcanic]; ...) and proper name formant ‘(a)n’: өt+(a)k+(a)n > өdugen odugen. Thus, we hold that “Odugen” meant the area containing the products of volcanic eruptions — volcanic lava and slag — the “excrement” of the Earth.